Accelerating Syntax Learning with Powtoon-Assisted Mnemonics - Muhammad Kafahulloh; Mohamad Zaka Al Farisi; Ali Abd al-Rubb Radman Taha (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2024)
This study aimed to tes the effectiveness of the mnemonic method combined with Powtoon learning media in enhancing students' understanding at Pesantren Darul Falah regarding syntactic material in Jurumiyah learning. The learning steps in this research include planning material, creating Powtoon content, making presentations and delivery, providing interactive exercises, repetition and memorization, evaluating learning, reflecting, and closing. A quasi-experimental method with a nonequivalent control group design and purposive sampling was used. The subjects included eighth-grade students from class VIII A as the experimental group and class VIII B as the control group. A validated multiple-choice test measured syntactic ability before and after the treatment. Data analysis using SPSS version 25 revealed a significance level of .000, indicating significant differences between the groups. The experimental group showed a greater improvement, achieving an N-Gain percentage of 77.40%, while the control group achieved 61.38%. These results indicated that the Powtoon-assisted mnemonic method effectively enhanced students' learning outcomes in syntactic mastery, whereas the mnemonic method alone was moderately effective. By combining visual animations and mnemonic elements, Jurumiyah learning becomes more interesting and easier for students to understand.